Isolation and screening of thermophilic cellulolytic bacteria from compost piles - Acharya, A; Joshi, DR; Shrestha, K; Bhatta, DR (Scientific World, 2012)
Cellulose, a major polysaccharide found in agricultural residues and industrial and municipal wastes. In the present study thermophilic cellulolytic microorganisms were isolated. The isolates were tested for their cellulytic activity. The enzyme production from potent isolates was optimised using cellulose basal broth medium. Activity of partially purified enzyme was determined. The most potent thermophilic cellulolytic isolates were identified as Bacillus subtilis. The crude cellulase enzyme concentrated at 80-85% ammonium sulfate produced highest zone of hydrolysis. The enzymatic degradation of cellulose waste has been suggested as a feasible alternative for the conversion of lignocelluloses substrate into fermentable sugars and application for biofuel production. Scientific World, Vol. 10, No. 10, July 2012 p43-46 DOI: http://dx.doi.org/10.3126/sw.v10i10.6861